Controlling Menstrual Pain Using Dysmenorrhea Physical Exercise in Young Women: In Young Women - Widyaningsih, Heriyanti Widya; Putri, Deshinta Laila; Wulan, Emma Setyo; Faidah, Noor (Jurnal Keperawatan Muhammadiyah, 2023)
Background: Adolescents in the age range 12 – 17 years are characterized by physical and psychological maturity. one of the physical maturity of adolescent girls since menstruation occurs and the growth of secondary sexual signs. Menstrual periods in teenagers can cause pain due to uterine contractions. The incidence of menstrual pain in Central Java is 56% which is quite high when compared to the incidence of primary menstrual pain in Indonesia. For young women, menstrual pain is at risk of causing learning disorders in the form of lack of enthusiasm, decreased concentration and even not going to school and can reduce the quality of life for teenagers. This research was conducted on young women at SMA N 1 Gebog Kudus to apply Evidence Based Practice (EBP) physical exercise for dysmenorrhea to reduce the incidence of menstrual pain. The research method uses a Quasi Experiment with a One Group Pre Test – Post Test research design. Three (3) methods were used to collect data with total sample, statifield random sampling and purposive sampling.Results: Based on the dysmenorrhea physical exercise treatment of 32 respondents, it was found that the average level of pain before being given dysmenorrhea physical exercise treatment was 6.88 and the average after treatment was 3.23. The average difference before and after is 3.63 with a p value of 0.000. These data show that there is a statistically significant difference in the average level of pain before and after dysmenorrhea physical exercise treatment.Conclusion: Menstrual pain in adolescent girls can be controlled with dysmenorrhea physical exercise activities.